Selectivity and Catch Efficiency of Three Spinner Hook Sizes in Angling for Rainbow Trout (Oncorhynchus mykiss Walbaum, 1792) in Karakaya Dam Lake (Eastern Turkey) - Atessahin, Tuncay; Duman, Erdal; Cilbiz, Mehmet (Central Fisheries Research Inst, 2015)
The aim of this study was to determine the relationship between spinner hook sizes (2, 3 and 4) and hook selectivity for Oncorhynchus mykiss (rainbow trout), a species important to recreational fisheries in Karakaya Dam Lake in Eastern Turkey. A total of 24 sampling trips were carried out twice per month by the same three anglers from May 2013 to April 2014. The SELECT method was used to determine the selectivity parameters. An analysis to determine the differences in the catch per unit effort (CPUE), yield per unit effort (YPUE) and condition factor values based on different hook sizes was conducted using one-way ANOVA. During the spinner hook-size experiments, we captured 202 Oncorhynchus mykiss, which ranged from 14.5 cm to 46.0 cm TL in length and weight 30.2 g to 1320.2 g. The mean lengths (+/- SE) of Oncorhynchus mykiss captured on the three spinner hook sizes were determined. The optimum lengths calculated by log-normal model were found to be 18.28, 27.41 and 36.55 cm for No 2, No 3 and No 4 hook sizes, respectively.
Karakaya baraj gölü gökkuşağı alabalığı'nın (Oncorhynchus mykiss Walbaum, 1792) üç farklı spinner iğne seçiciliği ve avcılık etkinliği
Keywords: Hook selectivity; Rainbow trout; Oncorhynchus mykiss; Catch efficiency; Karakaya Dam Lake